Spin-resolved electronic structure of ferroelectric α-GeTe and multiferroic Ge1−xMnxTe. (May 2019) - Krempaský, J.; Fanciulli, M.; Pilet, N.; Minár, J.; Khan, W.; Muntwiler, M.; Bertran, F.; Muff, S.; Weber, A.P.; Strocov, V.N.; Volobuiev, V.V.; Springholz, G.; et al.
Abstract: Germanium telluride features special spin-electric effects originating from spin-orbit coupling and symmetry breaking by the ferroelectric lattice polarization, which opens up many prospectives for electrically tunable and switchable spin electronic devices. By Mn doping of the α-GeTe host lattice, the system becomes a multiferroic semiconductor possessing magnetoelectric properties in which the electric polarization, magnetization and spin texture are coupled to each other. Employing spin- and angle-resolved photoemission spectroscopy in bulk- and surface-sensitive energy ranges and by varying dipole transition matrix elements, we disentangle the bulk, surface and surface-resonance states of the electronic structure and determine the spin textures for selected parameters. From our results we derive a comprehensive model of the α-GeTe surface electronic structure which fits to experimental data and first principle theoretical predictions and we discuss the unconventional evolution of the Rashba-type spin splitting upon manipulation by external B- and E-fields. Highlights: A simplified model of complex Rashba-type α-GeTe surface electronic structure is proposed A comprehensive ARPES study of bulk, surface and surface-resonance states is presented Spin-resolved ARPES is compared to ab-initio calculations and related with the proposed model The magnetic field switching of the (Ge, Mn)Te reveals complex spin switching behavior which we describe by the model.